2016
DOI: 10.1111/jeb.13008
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate sexual selection on male tegmina in wild populations of sagebrush crickets, Cyphoderris strepitans (Orthoptera: Haglidae)

Abstract: Although the strength and form of sexual selection on song in male crickets have been studied extensively, few studies have examined selection on the morphological structures that underlie variation in males' song, particularly in wild populations. Geometric morphometric techniques were used to measure sexual selection on the shape, size and symmetry of both top and bottom tegmina in wild populations of sagebrush crickets, a species in which nuptial feeding by females imposes an unambiguous phenotypic marker o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…In agreement with previous work on the same population of guppies in conditions similar to our control treatment [19,52], we found that sexual selection was largely nonlinear. Such pattern of disruptive selection, with multiple phenotypes being similarly advantaged, has been described in multiple taxa including insects [73], birds [74] and fish [75]. While we found no significant linear β regression coefficients or θ coefficients on the M vectors in either treatment (table 1; electronic supplementary material, table S5), comparisons between treatments revealed that selection on GTs and boldness was more strongly linear in the predation treatment, and opposite in direction, compared with control (electronic supplementary material, table S6).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with previous work on the same population of guppies in conditions similar to our control treatment [19,52], we found that sexual selection was largely nonlinear. Such pattern of disruptive selection, with multiple phenotypes being similarly advantaged, has been described in multiple taxa including insects [73], birds [74] and fish [75]. While we found no significant linear β regression coefficients or θ coefficients on the M vectors in either treatment (table 1; electronic supplementary material, table S5), comparisons between treatments revealed that selection on GTs and boldness was more strongly linear in the predation treatment, and opposite in direction, compared with control (electronic supplementary material, table S6).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study tested the relationship between acoustic signals in a sister species of field cricket, Teleogryllus commodus, and morphological features of male forewings that contribute to their resonant properties (Pitchers et al 2014). Such a pattern may be influenced by a greater degree of lability in behavioral traits compared to morphological traits that are fixed during development (Pitchers et al 2014;Ower et al 2016). Such a pattern may be influenced by a greater degree of lability in behavioral traits compared to morphological traits that are fixed during development (Pitchers et al 2014;Ower et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Pitchers et al (2014) found that wing morphology and acoustic signal properties covaried with differing strength in different populations of this species, but that overall covariance was minimal and appeared unrelated to patterns of population divergence. Such a pattern may be influenced by a greater degree of lability in behavioral traits compared to morphological traits that are fixed during development (Pitchers et al 2014;Ower et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Consideration of just one of these aspects, while being robust in the chosen field, may lead to unreliable interpretation of data (e.g. Ower et al, 2016). Some attempts have been made to infer basic singing parameters from Jurassic cricket species (Gu et al, 2012), but inferences are currently limited by a lack of knowledge on the characteristics of weakly delimited vibration-compliant areas.…”
Section: Resultsmentioning
confidence: 99%